Bowen’s disease with compact orthokeratosis at perianal region: a case report - Trevisan, Anna Luiza Lobo; Gomes, Nicole Silva; Swenson, Laura Ballalai; Paula, Natálya de; Finetti, Matheus Ribeiro; Venturelli, Laís Helena; Gonçalves, Gabriela Carlin; Miguel, Licério; Calixto Brandão Miguel, Marcela (Brazilian Journal of Case Reports, 2023)
Bowen’s Disease (BD) is an in situ squamous cell carcinoma (SCC) of epidermis, potentially malignant, which mainly affects sun-exposed areas. Nevertheless, the disease had an increased incidence in non-photo exposed areas, such as the anogenital region, correlating ambiental exposures, highlighting the Human Papillomavirus (HPV) infection as an important risk factor. BD has a positive prognosis according to its slow progress and prolonged time taken for full expression. In the anogenital region, presented in this case, the risk of invasive carcinoma is less than 6%. This case reports an unusual presentation of BD, describing a lesion with compact orthokeratosis in the anogenital region. The condition was diagnosed in a prevention routine of primary care attention, emphasizing the importance of premature diagnosis and satisfactory treatment, not just at BDs, but in a variety of conditions.